Multifaceted, unique role of CD11c in leukocyte biology - Hou, Lifei; Koutsogiannaki, Sophia; Yuki, Koichi (Frontiers in Immunology, 2025)
CD11c is widely known as a dendritic cell surface marker but its non-dendritic cell expression profiles as well as its functional role have been gradually delineated. As a member of leukocyte-specific β2 integrin family, CD11c forms a heterodimer with CD18. CD11c/CD18 takes different conformations, which dictate its ligand binding. Here we reviewed CD11c current state of art, in comparison to its sister proteins CD11a, CD11b, and CD11d, illustrating its unique feature in leukocyte biology.